Perkembangan Masa Puber - Kartika Mawar Nurhaliza; Nelfa Tri Safitri; Linda Yarni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research explores and evaluates Puberty, which is a time when a child experiences physical and emotional changes that indicate sexual and reproductive maturity. Puberty usually lasts around 9-14 years for girls and 12-16 years for boys. Hormonal changes during puberty cause various physical changes, such as breast growth, the appearance of acne, pubic hair, and height. Hormonal changes also cause emotional development, identity, and reproductive abilities. Deviant maturity can be caused by various factors, such as genetics, hormonal disorders, problems with the pituitary or thyroid gland, chromosomal disorders, eating disorders and so on. Early puberty can increase the risk of disease. Teenagers can experience the development of different characteristics, such as changes in body posture, height, and bone growth.